Autobiographical memories in major depressive disorder - Cláudio, Victor (2012)
The objective of this research was to study the relation between the processing and recall of information in major depressive disorder. An autobiographical memory task was applied to 42 subjects with a diagnosis of major depressive disorder, 28 subjects with a diagnosis of panic disorder and 51 subjects without any psychological disorder. We used clinical scales for the evaluation of depression and anxiety. The results of the three groups, and both assessment periods of depressed subjects, were compared. The results indicate the existence, in severely depressed subjects, of a bias in processing and recalling negative information. We associate this situation to the existence of negative contents in selfschemas and processing and recall of information consistent with these schema contents. Based on the obtained results, we consider that the onset and maintenance of depression is more related to the information encoding and recall processes, controlled by the self’s negative schemas, than with negative thoughts.